Benign strategy toward mesoporous carbon coated Sb nanoparticles: a high-performance Li-ion/Na-ion batteries anode - Dashairya, Love; Chaturvedi, Vikash; Kumar, Abhishek; Mohanta, Tandra Rani; Shelke, Manjusha; Saha, Partha (Solid State Ionics, 2023)
Antimony (Sb)-based anodes can offer excellent gravimetric capacity (-660 mAhg(1)) in lithium-ion/sodium-ion batteries (LIBs/SIBs) fabricated using carbonate-based electrolytes complexed with lithium/sodium salt. However, high first-cycle irreversible loss (35-40%) and gradual capacity fade (25-30%/cycle) originate from solid electrolyte interphase (SEI), and severe volumetric stress (-300%) associated with alloyed phase(s) impede reallife applications. Herein, we devise a benign strategy to develop mesoporous carbon coating onto antimony nanoparticles (Sb@C) based core-shell architecture for LIBs/SIBs anode. In particular, -30-50 nm thick mesoporous carbon spheres (-1 +/- 0.5 mu m) were obtained from resorcinol-formaldehyde (RF)-based polycondensation reaction by sol-gel chemistry engulfing Sb nanoparticles by suitably controlling Cetyltrimethylammonium bromide (CTAB)-induced steric stabilization and pH modulation during synthesis. The core-shell Sb@C helps faster Li+/Na+-ion migration preventing the structural collapse of Sb during electrochemical cycling and thereby improving the capacity fade. Electrochemical results demonstrate Sb@C can deliver a specific capacity of -536 mAhg(-1) and - 291 mAhg(-1) at 0.1C current rate in LIBs and SIBs, respectively, up to 200 cycles. Electrochemical impedance spectroscopy (EIS) indicates lower charge transfer (Rct) and SEI resistance (RSEI) of Sb@C cycled electrode than the bare Sb-NPs was the probable reason for improved Li/Na-ion storage in Sb@C anode. A detailed galvanostatic intermittent titration technique (GITT) and internal resistance measurements during 1st and 2nd cycles shed light on distinguishably different Li-ion/Na-ion storage behavior. The bulk Li+/Na+-ion diffusion coefficients found diminishes at reaction voltages (0.9 V/0.6 V for lithiation and 0.6 V/0.4 V for sodiation) corresponding with alloyed phase(s) concurrent with a drop in internal resistance at the quasi-opencircuit voltage (QOCV) during 1st and 2nd discharge cycle. On the contrary, de-alloying phenomena from the fully lithiated/sodiated phase(s) display an entirely opposite trend. The Li+ diffusion coefficient reaches minima at -1.1 V with a sudden jump in the internal resistance at QOCV during 1st and 2nd charge cycle. However, Na+ diffusion coefficient gradually drops along with a steep increase in the internal resistance, indicating partial Naion trapping and irreversible capacity loss.
Keywords: anode; Antimony; lithium-ion batteries; mesoporous carbon; Sodium-ion batteries